Clinical Applications of RNA Editing Technology for the Early Detection of Cancer and Future Directions - Ullah, Mujib (Technol Cancer Res Treat, 2020)
Early detection of cancer has great clinical importance and potentially improves cure, survival rate and treatment outcome. RNA editing technology can be used as targeted and precise molecular scissors to cut and replace disease-causing genes with healthy ones. This is a post transcriptional modification that can lead to the recoding of proteins. RNA editing technology is in its infancy, but it can be used for early diagnoses and effective treatment of cancer. The full potential of precision medicine will be achieved by using the knowledge of RNA reversible-recoding to edit the protein. RNA editing technology could be used to expose chemo resistant cancer cells, dormant cancer stem cells and other malignant tumors. RNA editing generates RNA and protein diversity to accelerate and enhance the screening window for early detection of cancer. We propose that the RNA editing sites could be used as a novel tool for early detection of cancer.